OPTIHEART: determinants and prognostic importance of optimal medical treatment in patients with heart failure with reduced ejection fraction discharged from a heart failure clinic from 2018 to 2020 - Alaa Sharfo; Astrid Lahn Sørensen; Emil Eik Nielsen; Ilan Esra Raymond; Anne Merete Boas Soja; Michael Hecht Olsen (Blood Pressure)
Background Heart failure (HF) is an increasing health problem globally. Profound sex-related differences have been observed regarding the cause, treatment, and prognosis of HF.Aim To assess baseline predictors for achieving optimal medical treatment (OMT) and the prognostic importance of OMT for male and female patients who have attended a HF clinical program (HFCP).Methods OPTIHEART was a retrospective study that included 870 consecutive patients with left ventricular ejection fraction (LVEF)≤40% discharged from HFCP in 2018, 2019 or 2020 and followed in registers for a mean of 1083(SD 11.3) days. OMT was defined as receiving an angiotensin-converting-enzyme-inhibitor (ACEi), angiotensin-receptor blocker (ARB) or angiotensin-II-receptor blocker and nephrylisin-inhibitor (ARNI) AND a betablocker (BB) both in doses ≥ 50% of target doses.Results Achieving OMT was associated with male sex (OR: 2.05 95%CI 1.44-2.97; p < 0.0001) independently of younger age, higher diastolic blood pressure (DBP), and lower creatinine. A lower rate of 5-point MACE was associated with achieved OMT (HR: 0.67 95%CI 0.50-0.90; p = 0.007) independently of female sex (HR: 0.64 95%CI 0.48-0.84; p = 0.002), younger age, never smoking and NYHA ≤ 2. The beneficial effect of OMT was insignificantly more pronounced in patients with male sex, older age, higher creatinine, lower DBP, and body mass index ≤25kg/m2.Conclusion OMT was more frequently achieved in patients with male sex independently of age, DBP, and creatinine. Achieving OMT was associated with less 5-point MACE independently of female sex, younger age, never smoking and NYHA ≤ 2.